2008
DOI: 10.1007/s10616-008-9125-4
|View full text |Cite
|
Sign up to set email alerts
|

Using EGFP fusions to monitor the functional expression of GPCRs in the Drosophila Schneider 2 cells

Abstract: In combining fluorescence measurements with ligand binding assays, the versatility of the EGFP C-terminally fused to the human mu opioid receptor (EGFP-hMOR) has been exploited to notably improve the expression level of functional G protein-coupled receptors in Drosophila S2 cells. A selected array of efficient optimization approaches is presented herein, ranging from a cell-sorting method, allowing for a substantial enrichment in EGFP-hMOR expressing cells, to the addition of chemical and pharmacological chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b. In previous publications Yokomizo et al, 2007) we have shown that the DES indeed represents a novel and promising approach for the production of the rabies virus glycoprotein (RVGP).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DES has been reported to have advantageous bioprocess characteristics, such as high cell density attained, low cost culture medium needed and continuous bioprocess possibility (Affleck and Walker, 2008;Batista et al, 2008Batista et al, , 2009Bovo et al, 2008;Brillet et al, 2008;Galesi et al, 2008;Iwaki and Castellino, 2008;Jorge et al, 2008;Park et al, 2008;Santos et al, 2007;Swiech et al, 2008aSwiech et al, , 2008b. In previous publications Yokomizo et al, 2007) we have shown that the DES indeed represents a novel and promising approach for the production of the rabies virus glycoprotein (RVGP).…”
Section: Introductionmentioning
confidence: 99%
“…Fermentation of Pichia pastoris cells has been optimized over years and it is possible routinely to obtain 100 g/l of dry cell weight whereas 5 g/l are obtained in flasks. The functionality of a recombinant GPCR is an important issue as recently discussed (Brillet et al 2008). In Pichia pastoris, the three beta-adrenergic receptor subtypes in fusion with EGFP were not able to bind specific ligands (data not shown) as for the human mu-opioid receptor fused to EGFP (Sarramegna et al 2005).…”
Section: Discussionmentioning
confidence: 91%
“…The simplest method involves the repeated treatment of a polyclonal population with high concentrations of the selection antibiotic in order to enrich for a high-producer subpopulation [ 6 ]. Cell lines expressing surface proteins can also be isolated using immuno-magnetic selection [ 5 , 45 , 46 ]. However, in both cases, the corresponding subpopulations remain polyclonal and are therefore still genetically inhomogeneous, possibly reducing the stability of protein expression over time due to differences in growth kinetics.…”
Section: Discussionmentioning
confidence: 99%